Pengaruh Strategi Promosi Terhadap Keputusan Pembelian Motor Yamaha Mio Pada PT. Hasjrat Abadi Tobelo - Duan, Remart R.; Kalangi, Johnny A. F.; Walangitan, Olivia F. C. (Sam Ratulangi University, 2019)
The purpose of this study was to determine the effect of promotion strategy on purchasing decisions of Yamaha Mio motors at PT Hasjrat Abadi Tobelo. PT. Hasjrat Abadi Tobelo launched the Matic type Mio Z, Mio M3 CW and Mio S types which are now popular in 2018. In 2017 Yamaha Mio sales were 428 units of motorcycles while in 2018 Yamaha Mio sales were 434 units of motorcycles, which means that in 2018 there was an increase in sales of Yamaha Mio. This research is a kind of quantitative descriptive research, using a correlation approach and simple regression, to see the relationship between variables and measure the magnitude of the influence that occurs in these variables. In the descriptive section of respondent's characteristics it can be seen that the respondents were the most female, namely 58.9%, respondents aged 20-30 years as much as 42.3%, and based on the latest education undergraduate students and respondents with civil servants (PNS) as much as 47% , is the respondent whose number is the most or dominant. Based on the results of the SPSS data the results of the determination coefficient or R Square (R2) are 0.379. From the equation above, it can be seen that if there are no independent variables that influence, promotion strategy 9,509 and every 1% increase in the promotion level, then the purchasing decision will increase by 0,791%. the results of simple linear regression analysis in the table above can be seen the results of calculations between promotional strategy variables on purchasing decisions can be arranged with the formula Y = a + bx which means Y = 9.509 + 0.791X. From the results above, the researcher gives the conclusion that promotional strategies are variables that influence purchasing decisions. This means that the higher the promotion strategy offered by Yamaha Mio, the higher the level of purchasing decisions.